Pengembangan Media Digital Storytelling pada Pembelajaran IPS SD untuk Membangkitkan Minat Belajar Generasi Millenial - Yelda Nurul Annisa; Bambang Hermansah; Imelda Ratih Ayu (Departement of Mathematics Education, 2024)
This development research aims to contribute knowledge about the development of digital media storytelling for students and for elementary school teachers. In addition, it can be used as input and reference material in the implementation of learning using learning media and motivating students Digital storytelling media is developed using the Powtoon application which contains images, animation, audio, text and video into one unit. The test subjects in this study were class III students, through the validation of media experts, material experts and language experts. The method used in this research is Developmental Research using the ADDIE (Analylis, Design, Development, Implementation, and Evaluation) model. The results of the development show that Digital Storytelling media is feasible to use based on the validation results of material experts, media experts, and language experts with a percentage of 88.83% Implementation of Digital Storytelling media is carried out on 26 students The implementation results show an overall percentage of 93.1% that the digital storytelling media developed is in the very practical category.